Flexible and printable dielectric polymer composite with tunable permittivity and thermal stability. Issue 15 (28th January 2020) - Hu, Feng; An, Lu; Chivate, Aditya Tushar; Guo, Zipeng; Khuje, Saurabh Vishwas; Huang, Yulong; Hu, Yong; Armstrong, Jason; Zhou, Chi; Ren, Shenqiang
Abstract : A printable dielectric polymer composite with enhanced dielectric constant and thermal stability. Abstract : Lightweight and printable polymer dielectrics are ubiquitous in flexible hybrid electronics, exhibiting high breakdown strength and mechanical reliability. However, their advanced electronic applications are limited due to their relatively low permittivity, compared to their ceramic counterparts. Here, we report flexible all organic percolative nanocomposites that contain in situ grown conductive polymer networks and dielectric polymer matrix, in which their dielectric properties can be designed and guided from the percolation theory. High dielectric constant of all organic percolative nanocomposites is shown over a broad frequency range under intensive bending cycles, while their thermal stability is attributed to thermally conductive 2D montmorillonite nanosheets. The printable polymer composites with high dielectric performance and thermal stability will find broader interest in flexible hybrid electronics and radio frequency devices.